CHARACTERISATION AND RATIONALISATION OF URBAN EFFLUENTS IN THE TIZI-OUZOU REGION (ALGERIA) - Aissaoui, D.; Metahri , M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The knowledge of the composition of urban wastewater discharges is an essential parameter to ensure the relevance of the choice and sizing of appropriate treatment systems to guarantee the quality objectives of the receiving environments. The results obtained allowed us to calculate the daily production per capita of physical, hydrocarbon, nitrogen and phosphorus pollution, specific to the study area. The values of the ratios calculated are : 30.02 g/IE/d for SM, 66.64% less than the reference discharge, i.e., 90 g/IE/d; 33.97 g/IE/d for BOD5, 43.38% less than the reference discharge, i.e., 60 g/IE/d; 53.80 g/IE/d for COD, 55.17% less than the reference discharge, i.e., 120 g/IE/d; 3.14 g/IE/d for TN, 68.28% below the reference value of 9.9 g/IE/d and 1.07 g/IE/d for TP, also 53.50% below the reference value of 2 g/IE/d. These results show that the calculated values reflect a different reality than the reference values. This approach could optimise the choice and sizing of treatment works.